THE INFLUENCE OF WATCHING CARTOONS ON THE DEVELOPMENT OF VOCABULARY IN EARLY CHILDHOOD - Sitorus, Leony; Damanik, Bernieke Anggita Ristia (Sindoro: Cendikia Pendidikan, 2025)
This study investigates the impact of cartoon viewing on vocabulary development in early childhood. Previous research has suggested that exposure to language-rich environments, including television programs, can contribute to vocabulary growth. However, the specific influence of cartoons, with their unique visual and auditory elements, remains a subject of exploration. To address this gap, this study examined the relationship between cartoon viewing frequency and vocabulary size in a group of young children. Using a combination of observational methods and vocabulary assessments, the findings suggest that regular cartoon consumption is positively correlated with vocabulary development, particularly when the cartoons are age-appropriate and feature diverse vocabulary. Children exposed to well-structured educational cartoons demonstrated a greater increase in vocabulary size compared to those with limited exposure. The implications of these results for parents, educators, and media producers are discussed, emphasizing the importance of selecting high-quality cartoon content to maximize language learning opportunities. This research highlights the potential of cartoons as valuable tools in early childhood education and advocates for a balanced approach to media consumption that promotes language development.